An investigation of tea factories' employees' motivation in the Nicaraguan (International Journal of Food and Nutritional Sciences, 2022)
In general employees are very sensitive to the level of care and concerns showed by the employers towards them i.e., in terms of ensuring safe, health and pleasant work environment, creating of various facilities, ensure work place infrastructures and health relationship with colleagues and seniors. It has been understood that business size and operational efficiency of the tea factory owners directly influences the level of pay and motivation employees receive. Realizing the prevailing situation of this agro-based production sector, researcher has developed interest in assessing nature of motivation employees in tea factories receive at present and how it support them in their commitment towards the organisation. A sample of 60 respondents from 10 tea factories functioning in Ooty region were surveyed. The research paper inferred that beside the monetary benefits an employees receives that influence them to work effectively and productively. Recognition, incentives and rewards (87.60 per cent), conductive work time (72 per cent), work infrastructure availability (79 per cent), establishment of basic facilities (canteen, toilet, rest room, medical room etc.,) (73.60 per cent) and prevalence of pleasant physical working environment (72.60 per cent) on the one hand. Co-operation received from all colleagues (80.60 per cent), opportunities to use of skills and abilities (74.60 per cent) and friendly supervisors/manager (73.60 per cent) on the other hand positively motivate tea factory employees in the Nilgiris district to be commitment and stay loyalty to their organisation (88.60 per cent).